Models of Intracellular Transport: Pros and Cons - Mironov, Alexander A.; Beznoussenko, Galina V. (Frontiers in Cell and Developmental Biology, 2019)
The intracellular transport is the most confusing issue in the field of cell biology. The Golgi complex (GC) is the central station along the secretory pathway. It contains Golgi glycosylation enzymes, which are responsible for protein and lipid glycosylation and in many cells it is organized into a ribbon. Here, we analyse the data related to the mechanisms of intracellular transport and evaluate different models of intracellular transport. Here, we deal only with those issues that are relevant to transport models and do not deal with molecular mechanisms.